Hubungan Antara Motivasi Kerja dan Disiplin Kerja dengan Kinerja Pegawai pada Kantor Kecamatan Citeureup - Widia Rahma; Teul Panda Banjal (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Teknologi Nusantara, 2025)
The decline in employee performance within government institutions is often influenced by low work motivation and discipline, as observed at the Citeureup District Office, Bogor. This study aims to analyze the effect of work motivation and work discipline on employee performance using a quantitative approach. The research employed a saturated sampling technique involving 52 respondents, while data were analyzed through validity and reliability tests, classical assumption tests, multiple linear regression, correlation, coefficient of determination, and hypothesis testing. The findings reveal that work motivation has a significant effect on employee performance, contributing 45.8%, while work discipline significantly influences performance by 53.2%. Simultaneously, motivation and discipline significantly affect performance with a determination coefficient of 60.9%, while the remaining 39.1% is explained by other factors. The regression equation obtained is Y = 9.165 + 0.314X1 + 0.463X2. These results highlight that strengthening both motivation and discipline is crucial for improving employee performance. The implication is that public sector management should formulate consistent policies that enhance motivation and enforce discipline to optimize service delivery and organizational goals.